2019
DOI: 10.1098/rsbl.2019.0004
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization between sympatric hammerhead sharks in the western North Atlantic Ocean

Abstract: Hybridization between closely related species has been documented across a wide range of taxa but has not been well studied in elasmobranchs. Hammerhead sharks have drawn global conservation concern because they experience some of the highest mortality rates among sharks when interacting with fisheries. Here we report on the detection of hybrids between the globally distributed scalloped hammerhead ( Sphyrna lewini ) and recently described Carolina hammerhead ( S. gilberti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
11
1
Order By: Relevance
“…Indeed, vicariant events caused by sea‐level changes (maximum 130 m) during this geological time have been recognized as responsible for speciation in several plant and animal lineages (Briggs & Bowen, 2013), including sharks (Domingues et al ., 2018, 2019). Nonetheless, there is no contemporary physical barrier to dispersal preventing contact between the two lineages, so more sampling between Belize and Mexico (Yucatan Peninsula) could reveal the extent of sympatry and possibly hybridization between these species, as has been seen in other shark species complexes (Barker et al ., 2019; Morgan et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, vicariant events caused by sea‐level changes (maximum 130 m) during this geological time have been recognized as responsible for speciation in several plant and animal lineages (Briggs & Bowen, 2013), including sharks (Domingues et al ., 2018, 2019). Nonetheless, there is no contemporary physical barrier to dispersal preventing contact between the two lineages, so more sampling between Belize and Mexico (Yucatan Peninsula) could reveal the extent of sympatry and possibly hybridization between these species, as has been seen in other shark species complexes (Barker et al ., 2019; Morgan et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…data) were beyond the scope of this study, and thus not reported here. Since S. lewini and S. gilberti are a cryptic species pair, fin clips were taken from every animal and preserved in a dimethyl sulfoxide solution for subsequent species genetic identification following the protocols of Barker et al (2019). Hybrid individuals and those with indeterminant genetic discrimination where liver samples were taken for lipid extraction were removed from the data set (n = 14; Supplemental Table 1).…”
Section: Sample Collectionmentioning
confidence: 99%
“…Temporal and geographical growth patterns in YOY were explored using a larger data set from Barker et al (2019). Since this data set did not include scar healing or condition information, only date of sampling, fork length, location and species identification information were used.…”
Section: Growth Dynamics Across Nurseriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their divergence was estimated to have occurred 4.5 million years ago (Pinhal et al ., 2012; Quattro et al ., 2013). In addition, these species are capable of hybridization (Barker et al ., 2019). Because of the morphological similarity, S. gilberti was described only recently from the Carolina coasts (South and North Carolina states, USA) in the western North Atlantic Ocean (Quattro et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%